Keratella cochlearis hispida (Lauterborn, 1898): A new record for Turkish Rotifer fauna - Saler, Serap; Bulut, Hilal (Universitatea din Oradea, 2017)
Rotifera species collected from Keban Dam Lake 65 km far away from Elazig were surveyed taxonomically and fifteen taxa were identified. One of these taxa Keratella cochlearis hispida (Lauterborn, 1898), is new record for Turkish rotifer fauna. © 2017 Biharean Biologist, Oradea, Romania.
Keywords: Diagnostic differences; Keratella cochlearis; Keratella cochlearis hispida; Rotifera